2010
DOI: 10.1002/btpr.386
|View full text |Cite
|
Sign up to set email alerts
|

A rotating bed system bioreactor enables cultivation of primary osteoblasts on well‐characterized sponceram® regarding structural and flow properties

Abstract: The development of bone tissue engineering depends on the availability of suitable biomaterials, a well-defined and controlled bioreactor system, and on the use of adequate cells. The biomaterial must fulfill chemical, biological, and mechanical requirements. Besides biocompatibility, the structural and flow characteristics of the biomaterial are of utmost importance for a successful dynamic cultivation of osteoblasts, since fluid percolation within the microstructure must be assured to supply to cells nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Furthermore, fluid flow within the culture vessel could provide mechanical stimulation of the cells [21, 22]. Perfusion bioreactors are widely used for in vitro cultivation of three-dimensional tissues [17-19] and for cell expansion under GMP conditions [20]. Several other studies have shown enhanced synthesis of matrix proteins in three dimensional cultures in perfusion bioreactor systems as compared to static culture systems [38-40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fluid flow within the culture vessel could provide mechanical stimulation of the cells [21, 22]. Perfusion bioreactors are widely used for in vitro cultivation of three-dimensional tissues [17-19] and for cell expansion under GMP conditions [20]. Several other studies have shown enhanced synthesis of matrix proteins in three dimensional cultures in perfusion bioreactor systems as compared to static culture systems [38-40].…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion bioreactor systems are widely used for the cultivation of cells on scaffold materials for the in vitro fabrication of tissue engineered constructs [17-19]. Insufficient migration and growth of cells into the scaffold and insufficient nutrient transport, especially to the interior of the carrier material cultured under static conditions, can be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…For bone tissue engineering, several approaches such as rotational reactors, perfusion reactors, or stretch and pressure chambers have been used to imitate the physiologic environment for bone formation and repair. 6,14,15,19,4648 Besides the successful cultivation of bone substitutes in various other reactor types, perfusion culture is still the most common concept used for bone tissue engineering. 4 Several other bioreactor models have been already characterized by CFD modeling of internal flow and pressure distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results are consistent with previous reports on the cultivation of tissue-engineered bone substitutes in perfusion bioreactors. 6,16,17,20,23,52 The problem relating to low yields of new tissue formation in a bioreactor may also be related to using a stiff matrix that can induce the early differentiation of stem cells, and the mono-cellular culture system which is not mimicked by nature in the same way. We propose that our system is suitable for studies of mechanical forces on cell proliferation and differentiation in a defined flow and pressure environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an adequate supply with nutrients should be maintained. Currently, commercial and tailor‐made bioreactors used for bone TE are rotating‐wall vessels [55, 61, 73, 74], rotating beds [53, 75], spinner‐flask systems [55, 61, 73, 76, 77], and direct perfusion systems [61, 77–79], among others. In rotating‐wall and spinner‐flask bioreactors, sufficient transport of nutrients cannot be guaranteed into the inner part of scaffolds with clinically relevant sizes [55].…”
Section: Control Of Culture Conditions – Musculoskeletal Applicationsmentioning
confidence: 99%